Perilaku Solusi Sistem Persamaan Diferensial Waktu Tunda Dinamika Virus HIV Dalam Sel Tubuh - Tambunan, Lidia Veronika; Sinaga, Lasker Pangarapen (Universitas Negeri Medan, 2018)
The dynamics model of the HIV-virus without delay in the cells of the human body has a critical point in two conditions, namely virus-free conditions and endemic conditions. Based on stability analysis with eigenvalues and Routh Hurwitz criteria, these two critical points are asymptotically stable. With a graph of the behavior of the HIV-virus model dynamics solution with time delay shows asymptotic stable behavior. Observations were made with numerical simulations (Forward Euler method) based on the selection of parameter values randomly and the delay time randomly. Graph behavior of infected cell solutions and increased plasma viruses causes a graph of healthy cell solutions to decrease and vice versa. Based on the analysis and simulation conducted, it appears that the solution modeled the dynamics of the HIV-virus without delay and with the delay time moving towards the equilibrium point or called asymptotically stable. The provision of greater delay causes the number of infected cells and plasma viruses to decrease significantly and on this occasion, the number of healthy cells can increase.